(untitled) (Journal of Laboratory Animal Science, 2022)
In the recent years, zebrafish (Danio rerio) species has been popularized as an animal model of human biology in understanding the genetic mechanism of vertebrate development and disease. Aquarium water is an immediate surrounding medium for the fish species in laboratory setup that determine their survival and normal physiological activities. Raising healthy zebrafish in the laboratory environment is prerequisite to ensure disease free stock for better research outcome. Important water parameters such as temperature, pH, electric conductivity, salinity, dissolved oxygen and CO2 are required to be monitored regularly as a part of quality control. An episode of acute mortality was witnessed in several lines of laboratory zebrafish maintained at the facility of TIFR, Mumbai. The clinical symptoms include lethargy, swimming inability, settling down at the bottom and acute death. The acute mortality was evidenced irrespective of age, sex and strains of the zebrafish. The investigation was carried out to find the etiological agents implicated in the acute mortality. After ruling out various causative agents associated with the mortality, an investigation was zeroed on the pH of the fish aquarium water, the culprit for the acute death episode. The highly acidic pH (3.5 to 4.0) of the fish aquarium water was brought to normal level by adding buffer solution to avoid further mortality. Present paper describes an episode of acute death, timely diagnosis and successful measures taken to rescue the Danio rerio loss due to highly acidic aquarium water.